WHO ARE THE SPOILERS OF THE PEACE? THE CASE OF CIVIL CONFLICT IN ANGOLA - Kucerova, M. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The paper deals with the topic of spoilers identified as the specific type of the actors of civil conflict by Steven John Stedman. This concept describes spoilers as actors who by using violence spoil an ongoing peace process in a country. However, by this operationalization it is possible to identify the spoiler only after he started to act and this is one of the core critiques of this concept. The goal of the text is to analyze the characteristics of spoilers with the aim to identify whether this type of actors of civil conflict differ in some important characteristics form the other actors active in civil conflicts. My analysis suggests, there is no important difference between the identified spoiler and other actors fighting in civil war and thus there is no possibility to identify who will become the spoiler of the peace process.